Risiko dan Peluang Industri Makanan Rumah Tangga dengan Sistem On-Line dalam Masa Pandemi Covid-19 di DIY - Widyaningrum, Rachmawati (Journal of Food and Culinary, 2021)
Background. During pandemic Covid-19, the online delivery and ordering system in the household food industry is an alternative for fulfilling the consumer’s food requirement without leaving their house. Further, the household food industry also works as a national economic trigger. However, concern about food safety, virus transmission, and halal-food status is still challenging with the low number of the household food industry that has been registered and has a halal certificate.Objectives. This study aimed to understand the perceptions of the stakeholder of the online selling system of the household food industry the pandemic of Covid-19 due to: 1) Risk of product’s safety and Halal status 2) Economic opportunity 3) Management system to minimize risk and optimize the opportunity. Method. The research was a descriptive qualitative study conducted through an online interview held in January-February 2021. Respondents are the household food industry’s producers in DIY, conducting commercial household food production during the pandemic, doing online selling, and did not have an offline store. The subjects were recruited using the purposive sampling method. Data triangulation was applied using a deep interview with consumers, food safety, and halal food expert.Results. The household food industry during pandemic brings a positive effect on the household's economic strengthening and entrepreneur opportunity. Food safety and halal food issues arise from a lack of knowledge of the producer, resource limitation, and uncertified products. These risks could be minimized through sustainable collaboration between producers, consumers, and the government for actualizing halal and safe food production.